The Asymmetric Effects of Exchange Rate Fluctuations : Theory and Evidence From Developing Countries - Kandil, Magda (IMF Working Papers; Working Paper, 2000)
The paper examines the asymmetric effects of exchange rate fluctuations on real output and price in developing countries. The theoretical model decomposes movements in the exchange rate into anticipated and unanticipated components. Unanticipated currency fluctuations determine aggregate demand through exports, imports, and the demand for domestic currency, and determine aggregate supply through the cost of imported intermediate goods. The evidence indicates that the supply channel leads to output contraction and price inflation in the face of unanticipated currency depreciation. In contrast, the reduction in net exports determines output contraction without reducing price inflation in the face of unanticipated currency appreciation.